Design and analysis of cooperative wireless data access algorithms in multi-radio wireless networks - Lee, Kiwon; Jang, Insun; Pack, Sangheon; Lee, Wonjun (Wireless networks, 2013)
In the future, most mobile nodes will have multiple radio interfaces, and this feature can be exploited to reduce the transmission cost in wireless data access applications. In this work, we propose cooperative poll-each-read (CoopPER) and cooperative callback (CoopCB) wireless data access algorithms with strong consistency in multi-radio wireless networks. In addition, we investigate CoopPER and CoopCB in heterogeneous wireless networks where CoopPER and CoopCB nodes are mixed. Extensive simulations are done to show the effects of access-to-update ratio, data access pattern, cache size, and cooperation range. Simulation results demonstrate that CoopPER and CoopCB can significantly reduce the expensive transmission cost over wireless links.